Kadar Glukosa Darah Berhubungan dengan Fungsi Kognitif pada Pasien Diabetes Mellitus - Aulia Asyifa Nanda; Okti Sri Purwanti (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the relationship between blood glucose levels and cognitive function in patients with diabetes mellitus. The method used is a correlational analytic study using a cross-sectional approach. The results showed that respondents with high fasting blood sugar and normal cognitive were three, and those with high fasting blood sugar and cognitive impairment were 39. If the total was added up, 42 (62.68%) respondents had high fasting blood sugar. Based on the results of the chi-square test, the value of Sig. (2-tailed) 0.001 < (p-value 0.05). In conclusion, a relationship exists between blood glucose levels and cognitive function in diabetes mellitus patients. Keywords: Diabetes Mellitus, Cognitive Function, Blood Glucose Level